CONTRADICTIONS OF THE EUROPEAN MEDIA POLICY - Milutinović, Irina R (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2018)
In the media theory and practice, there is a broad agreement that the media play an important role in creating of active public, which is perceived as а social and political space in which public opinion is created and acted. The focus of this paper is on the question: does the European media policy coherently, consistently and comprehensively implement its programs in line with projection that the media have status and responsibility of the “fourth government” or “watchdogs of democracy” in a democratic society? The aim of the paper is to discuss compatibility between, on the one hand, proclaimed norms and principles of the European media policy, and on the other, success of their practical realization in the function of democratic public. Methods of critical and comparative analysis have been applied, and the following indicators have been considered: media market liberalization, state protectionism, media corporatism, social and media pluralism, public interest. In the conclusion, several factors that disturb coherent implementation of the media policy in the pan-European framework are identified: ineffectiveness of the foreseen instruments; a lack of democratic legitimacy; divergent interests of individual actors in the media sector, and fundamental differences among individual member states with reference to the social and economic functions of the media.
Keywords: media policy; free market; media ownership; pluralism; public interest; European Union; Council of Europe